Conversion of carbon dioxide gas to hydrocarbon fuels by electrolysis in molten salts - Al-Juboori, Ossama Hussein Ali (2019)
Using fossil fuels in power generation has not been considered a serious issue until recent justification of the depletion of fossil resources in addition to the rising atmospheric temperature as a result of increasing CO2 emission from fossil fuel consumption. Technologies that can absorb CO2 from the emissions and, more substantially, convert CO2 economically into useful products, e.g. materials or fuels, with lower carbon intensity are urgently needed and more desirable than simply storing the gas underground. Performing such conversion at high temperatures (200-600 oC) can offer both thermodynamic and kinetic advantages. Molten salts are ideal media for high temperature reactions but their use for the conversion of CO2 and H2O to beneficial products has not yet been examined properly. Thus, this research aims to investigate the feasibility of producing hydrocarbons by the electrochemical reduction of CO2 and H2O (steam) in molten salts at the atmospheric pressure. Two different mechanisms were suggested in literature for hydrocarbon formation after the co-electrolysis of CO2 and H2O to CO or C (carbon) and H2 in molten salts. The first one is the partial oxidation of CH4 that is produced feasibly in molten salts (e.g. C+2H2=CH4). Due to the sufficient availability of oxide ions (O2-) in molten salts, where the partially reduced species of oxygen (O2-, O22-) are obtained, the produced CH4 can be transferred to C2 and other hydrocarbons by the catalytic oxidative coupling in liquid phase. However, there is a possibility of CH4 reaction with O2 to CO2 and H2O. The second mechanism is the direct reaction of carbon with atomic hydrogen adsorbed primarily on the cathode producing different hydrocarbons. However, some other studies detected CH4 attached with slight amounts of long-chain hydrocarbons in the cathodic gas product during the direct electrolysis of molten carbonates mixed with hydroxides. The electrolyser used in this work resembled that for CO2 reduction to CO in lithium containing molten carbonates at 900 oC using a cell with partitioned cathode and anode compartments. However, in addition to the ternary molten carbonates (Li2CO3-Na2CO3-K2CO3) of (43.5:31.5:25 mol%), this work also studied the molten chloride salts of KCl-LiCl of (41:59 mol%) and molten hydroxides of LiOH-NaOH (27:73 mol%) and KOH-NaOH (50:50 mol%). The electrolyser was employed at different temperatures (220-600 oC) depending on the molten salt applied. Various cathodic gases were produced during the electrolysis as confirmed by gas chromatography. At the specified temperatures in this work, olefin hydrocarbon species between (C2-C5) rather than paraffins were found (as the reaction of CO with H2 is feasible) by a total production rate of 0.06 mmol/h of the whole product associated with H2 and CO in molten carbonate electrolysis at 1.5 V and 425 oC under a feed gas of 15.6 molar ratio of CO2/H2O. The priority of olefin formation can be confirmed also by the mechanism of partial oxidation of CH4. The summation of current efficiencies for different cathodic products was close to 100%. The CH4 gas was the predominant hydrocarbon fuel produced during the electrolysis in molten hydroxide in general. No significant indication of hydrocarbon formation was found in the molten chlorides from CO2 reduction or conversion even at 1.3 bar of CO2. The effect of the molten salt temperature, applied electrolysis voltage and the CO2/H2O ratio of the feed gas were also examined during the electrolysis in molten carbonates and hydroxides. By increasing the electrolysis temperature from 425 oC to 500 oC, the number of carbon atoms in the hydrocarbon species produced in the cathodic gas rose to 7 (C7H16) with a production rate of 1.5 μmol/cm2.h at a CO2/H2O ratio of 9.2 increasing the average molecular weight of the product and thus the calorific value. However, the hydrocarbon fuel content in the cathodic gas product in general was found to be higher in the case of high inlet gas CO2 content (CO2/H2O=15.6) by 18% at 425 oC and 41% 500 oC which can be considered as the optimum condition for hydrocarbon formation in this research. Due to the prospective carbon formation, the electrolysis to produce hydrocarbon in molten carbonates was more feasible at 1.5 V than that performed at 2 V. In molten hydroxide case, the CH4 production rate increased when the applied voltage was increased from 2.0 to 3.0 V despite the reduced current efficiencies. Because the electrolytic conversion can be very fast and achieved without using any catalyst, such as the precious metals used in other CO2 reduction routes in water, the results reported in this thesis are promising and encouraging for further fundamental investigation and technological development.